Pengaruh Brand Image, Digital Marketing dan Harga Terhadap Keputusan Pembelian Produk Skintific Cosmestic Pada Mahasiswa Prodi Manajemen Universitas Methodist Indonesia - Nadeak, Sepriani; Sabrina , Hesti (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to determine the influence of brand image, digital marketing, and price on purchasing decisions for skintific cosmetic products among students majoring in management at Methodist University of Indonesia. Brand image, digital marketing, and price are three important factors that can influence purchasing decisions. The population in this study were 713 students of the Management Study Program at Methodist University of Indonesia from 2021 to 2024. The number of samples in this study were 99 students of the Management Study Program, Methodist University of Indonesia with the criteria of Methodist Indonesia Management Study Program students using Skintific cosmetic. The data analysis techniques used in this study were descriptive analysis techniques and statistical analysis techniques. The data collection method in this study was through interviews, questionnaires, and documentation studies. The results of this study indicate that the influence of brand image, digital marketing, and price simultaneously had a significant effect on purchasing decisions with an F count of 296.549 > F table 2.71. The test conducted showed that brand image, digital marketing, and price partially had a positive and significant effect on purchasing decisions. The Adjusted R Square value obtained from the Coefficient of Determinant (R^2) test for purchasing decisions was 0.914, meaning 91.4% can be explained by brand image, digital marketing, and price. The remaining 8.4% can be explained by other factors not examined in this study.